PERAN STRATEGI PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN PADA PT ALFAMART KUTACANE - Desy Lopiga; Nasruddin Nasruddin; Bahrul Ilmi (CV. Armas Suan Sejahtera, 2025)
In an effort to retain its customers, PT. Alfamart is required to be responsive and meticulous in understanding customer desires and satisfaction. Alfamart runs weekly promotions every month. The researcher wanted to determine whether these weekday promotional prices have an impact. Meanwhile, with the increasing competition, minimarkets in Medan often publish brochures containing promotional prices at specific times. The purpose of this study was to determine and analyze